Conformational transitions in the γ subunit of the archaeal translation initiation factor 2. (1st March 2014) - Nikonov, Oleg; Stolboushkina, Elena; Arkhipova, Valentina; Kravchenko, Olesya; Nikonov, Stanislav; Garber, Maria
<x xml:space="preserve">Abstract</x> In eukaryotes and archaea, the heterotrimeric translation initiation factor 2 (e/aIF2) is pivotal for the delivery of methionylated initiator tRNA (Met‐tRNAi) to the ribosome. It acts as a molecular switch that cycles between inactive (GDP‐bound) and active (GTP‐bound) states. Recent studies show that eIF2 can also exist in a long‐lived eIF2γ–GDP–Pi (inorganic phosphate) active state. Here, four high‐resolution crystal structures of aIF2γ from Sulfolobus solfataricus are reported: aIF2γ–GDPCP (a nonhydrolyzable GTP analogue), aIF2γ–GDP–formate (in which a formate ion possibly mimics Pi), aIF2γ–GDP and nucleotide‐free aIF2γ. The structures describe the different states of aIF2γ and demonstrate the conformational transitions that take place in the aIF2γ `life cycle'.